The kiln - Armstrong, Jennifer, 1961- (Armstrong, Jennifer, 1961- Fire-us trilogy, 2003)
After a virus destroys most of the world's adult population, a band of children travels in search of an explanation for the dark mystery that forms the heart of their existence.